Profile Shaped-configuration of Convex Ellipse Rotor and Its Following High-shape Technology - Xiangjun Yang; Fuchun Sun (Jixie chuandong)
For higher effective volume ratio of roots pump， from high output production and low inner leakage， the shaped-profile configuration of a ellipse basic rotor and its raised rotor of is constructed. Firstly， from ellipse coordinate equation of rotor shaped-profile and conjugate principle of rotor pairs and critical conjugate conditions， the optimum axial length ratio of ellipse arc and the maximum shape coefficient of basic rotor are calculated. Secondly， based on the geometric relationship when the endpoint of valley working shaped-profile on driving rotor is just perfect to avoid the peak corner point on driven rotor， the maximum shape factor of raised rotor under a given addendum angle is determined. Finally， all parameter coordinate equations of raised shaped-profiles are provided， and the comparative advantage results of raised rotor to common circular arc rotor is focused on. All results show that the elliptical arc foundation rotor and high-profile rotor profile construction method have significant improvement in both high yield and leakage prevention effects， and the fundamental problem of the optimal axial length ratio and maximum shape factor of the arcs arc of the Roots pump is solved.